Application of Public Health theory in a Rural Population for Program Development at the Wellness Partners (a Corporate Wellness Company) - Banks, Abby (My University, 2013)
My public health field experience was conducted in McCook, Nebraska at a corporate wellness company called the “Wellness Partners.” They are hired by other companies (which I will often refer to as employer groups or clients) to help them offer wellness incentives to their employees. Of the services I will list in a moment, a company can chose which ones they would like to purchase and offer their staff members. The majority of our clients opt for the entire package and offer their employees discounts on insurance for participating in the program. (I will often refer to the employees who chose to enroll in the program as “participants.”) Wellness Partners is quite small, employing approximately 40 people. The owners started out in the insurance industry and by way of intuition saw the opportunity for their clients to lower health costs by improving employee health. In order to meet this need, they started up the Wellness Partners as a separate business. The company has been in operation for ten years. The strategies they have already developed are quite successful and the company finds itself in high demand and needing to establish a growth plan that will allow them to take on larger employer groups. When I first talked with the owner, I was impressed to find that someone with no public health background was able to construct such successful strategies for intervention-based wellness. From my educational research on the topic, I could tell that this company was using some of the most successful strategies the industry has to offer. The Wellness Partners offers a long list of services including health fairs, flu shot clinics, a comprehensive health risk assessment and accompanying lab tests, monthly publications and wellness challenges, and data management. One unique service that they are able to offer because of their size is individualized counseling. Every employee that chooses to participate in the wellness program has access to one-on-one calls with a registered nurse, dietician, exercise physiologist, and employee advocate. A need for extra intervention for high risk employees led to the creation of the Health Boost program. A large portion of my practicum focused on the Health Boost program. Health Boost is an additional program that is offered as a part of the full package to employer groups. It was developed in order to give extra support to those employees who are “high risk” or have the largest probability of costing their employer extra money in health care costs. An employee must fulfill one of the following criteria to enroll: • Diagnosed Diabetic (Fasting blood glucose (FBG)>125), • Pre-Diabetic AND Obese ( FBG> 110-125 AND BMI>30), or • Hypertensive: Blood Pressure 160/100 mm Hg or higher. Anyone meeting these criteria can be invited to join Health Boost which provides them with quarterly A1C kits (diabetics only), nurse consultations and unlimited access to the Health Boost team. The Health Boost team consists of a dietician, exercise physiologist, and mental health counselor who all collaborate for highly individualized wellness plans for the participants. Currently, the primary focus of the program is disease management. Weight management is a large contributor to disease management; however, has not been emphasized as an actual goal of the program. The company is looking to expand the program in two ways. First, they want to open up the program to anyone who is morbidly obese (BMI>40) regardless of comorbidities. Second, they would like to add a weight management program to the existing strategies in Health Boost that would be offered to all Health Boost participants old and new. This new program is to be delivered primarily through print materials and should increase the reach and efficiency of the Health Boost program.
Keywords: Public Health; Rural Populations; Wellness; Public Health (0573)